G-C3N4@PMo12 composite material double adjustment improves the performance of perovskite-based photovoltaic devices. (October 2020) - Xu, Xueying; Xie, Mingye; Xu, Kaicheng; Zhao, Yue
Graphical abstract: The polyoxometalate-based composite g-C3 N4 @PMo12 was prepared by ultrasonic method. The composite can not only promote the separation of photogenerated carriers, improve the electron migration rate, but also passivate the defect density and reduce the interfacial electron recombination, thus obtaining high quality films with large grain size. by adding g-C3 N4 @PMo12, to the perovskite layer to improve the performance of perovskite-based optoelectronic devices. Highlights: The addition of g-C3 N4 not only improves the morphology of perovskite crystals, but also passivates the defect states. The addition of polyoxometalate PMo12 not only improves the problem of mismatch between the energy levels of g-C3 N4 and the perovskite layer, but also improves the light absorption of the perovskite layer. The grain size of the modified perovskite layer increased from 100 nm to 300 nm. The photocurrent of the device has increased from ~4.5 μA to ~11.5 μA. Abstract: At present, reducing the defect density at grain boundaries is still the main method to improve the performance of perovskite photodetectors. The increase of grain size can also improve the performance of perovskite photodetectors. In this work, we added POM @ g-C3 N4 as a dopant into the perovskite precursor solution for the first time. The doping of g-C3 N4 can control the crystallization rate of perovskite, thereby passivating the charge recombination center at the grain boundary to reduce the defect density. However, the conduction band energy level of g-C3 N4 is higher than that of perovskite, which is not conducive to electron transmission. Polyoxometalate (POM) H3 PMo12 O40 (PMo12 ) has very good ultraviolet–visible light absorption. Adding it to perovskite can improve the ultraviolet–visible light absorption of the perovskite layer. Furthermore, the energy level of the polyoxometalate PMo12 matches the perovskite layer, which promotes the electron transport. Adding the composite material to the perovskite precursor solution not only increases the grain size of the perovskite crystals from 100 nm to 300 nm, but also increases the light absorption of the perovskite layer. Consequently, the photocurrent increased from 4.5 μA to 11.5 μA under the double regulation of the composite material, which is 2.6 times of the photocurrent of the reference group. This work provides a method of double adjustment of composite materials to increase the photocurrent of photodetectors.